The Essential Elements in a Community of Enquiry - A Study of Computer-supported Collaborative Learning in Higher Education - Shariman, , Tengku Putri Norishah Tengku (2005)
The aim of this research is to design an effective model for the development of a community of enquiry in institutions of higher education in Malaysia. This paper describes how a community of enquiry could simulate, and promote higher order thinking and reasoning skills among students. It is our interest to study the required elements that are essential to develop a community of enquiry within a computer-supported collaborative learning (CSLC) environment, and how the implementation of this model would benefit the students' performance, comprehension, and critical learning skills.